Pelayanan Kesehatan Pada Ibu Hamil Dengan Risiko Tinggi: Systematic Review - Marissa, Febi; Kusumawaty, Ira (JKM : Jurnal Keperawatan Merdeka, 2023)
Background: One of the efforts to support the acceleration of the decline in maternal mortality and neonatal mortality is to optimize the handling of obstetrics and neonatal emergencies/complications at the basic service level through the Basic Neonatal Emergency Obstetrics Service (PONED). The purpose is to see about health services in pregnant women with high risk. This article uses a systematic review approach Methods: Articles were searched through electronic databases systematically in ScienceDirect and PubMed using the keywords (((((('Obstetrics) OR (''Essential)) And ("Pregnancy'') OR ("High risk")), Results: Based on the results of data extraction from search engine methods Science Direct and Pub Med there were 15 journals selected based on inclusion criteria. Conculusion: Maternal and infant mortality rates are considered important indicators reflecting socioeconomic and infrastructural conditions, but especially the quality of health systems and services, in particular health care, since they have attributes that define them with greater diagnostic sensitivity and high solvability. Keywords: Health services, pregnant women, High risk